A Barbourin-albumin Fusion Protein that Is Slowly Cleared In Vivo Retains the Ability to Inhibit Platelet Aggregation In Vitro - Marques, Janey A.; George, Jacob K.; Smith, Ian J.; Bhakta, Varsha; Sheffield, William P. (Thrombosis and Haemostasis, 2001)
Barbourin is a 73 amino acid venom protein that inhibits platelet aggregation. Recombinant barbourin (BARH6), rabbit serum albumin (RSAH6), and a barbourin-RSA fusion protein (barbourin-linker-albumin; BLAH6) were secreted from Pichia pastoris yeast, and purified by nickel-chelate affinity chromatography via their C-terminal hexahisti-dine (H6) tags. BARH6 and BLAH6 did not differ in their IC50s for inhibition of platelet aggregation using either human platelets stimulated with thrombin or ADP, or rabbit platelets stimulated with ADP. BARH6 and BLAH6 were also effective in inhibiting platelet aggregation in whole blood, and formed complexes with platelet integrin αIIbβ3. The terminal catabolic half-life of BLAH6 approached that of RSAH6[3.4 ± 0.2 versus 4.0 ± 0.1 days (n = 4 ± SD)], but was substantially increased relative to that of BARH6 [0.15 ± 0.03 days (n = 3 ± SD)]. Our results suggest that fusion to albumin slows the clearance of barbourin in vivo, while preserving its ability to inhibit platelet aggregation.
Keywords: Barbourin; disintegrins; albumin; clearance